Authority - Walzer, Michael; Lorberbaum, Menachem, 1958-; Zohar, Noʻam; Lorberbaum, Yair (Jewish political tradition, 2000)
This book launches a landmark four-volume collaborative work exploring the political thought of the Jewish people from biblical times to the present. Each volume includes a selection of texts-from the Bible and Talmud, midrashic literature, legal responsa, treatises, and pamphlets-annotated for modern readers and accompanied by new commentaries written by eminent philosophers, lawyers, political theorists, and other scholars working in different fields of Jewish studies. These contributors join the arguments of the texts, agreeing or disagreeing, elaborating, refining, qualifying, and sometimes repudiating the political views of the original authors. The series brings the little-known and unexplored Jewish tradition of political thinking and writing into the light, showing where and how it resonates in the state of Israel, the chief diaspora settlements, and, more broadly, modern political experience. This first volume, Authority, addresses the basic question of who ought to rule the community: What claims to rule have been put forward from the time of the exodus from Egypt to the establishment of the state of Israel? How are such claims disputed and defended? What constitutes legitimate authority? The authors discuss the authority of God, then the claims of kings, priests, prophets, rabbis, lay leaders, gentile rulers (during the years of the exile), and the Israeli state. The volume concludes with several perspectives on the issue of whether a modern state can be both Jewish and democratic. Forthcoming volumes will address the themes of membership, community, and political vision. Among the contributors to this volume: Amy Gutmann Moshe Halbertal David Hartman Moshe Idel Sanford Levinson Susan Neiman Hilary Putnam Joseph Raz Michael Sandel Allan Silver Yael Tamir.